Microbial diversity of meat products under spoilage and its controlling approaches - Zhu, Yanli; Wang, Wei; Li, Ming; Zhang, Jiamin; Ji, Lili; Zhao, Zhiping; Zhang, Rui; Cai, Demin; Chen, Lin (Frontiers in Nutrition, 2022)
Meat spoilage (MS) is a complex microbial ecological process involving multiple specific microbial interactions. MS is detrimental to people's health and leads to the waste of meat products which caused huge losses during production, storage, transportation, and marketing. A thorough understanding of microorganisms related to MS and their controlling approaches is a necessary prerequisite for delaying the occurrence of MS and developing new methods and strategies for meat product preservation. This mini-review summarizes the diversity of spoilage microorganisms in livestock, poultry, and fish meat, and the approaches to inhibit MS. This would facilitate the targeted development of technologies against MS, to extend meat's shelf life, and effectively diminish food waste and economic losses.